Superhydrophobic copper foam bed with extended permeation channels for water-in-oil emulsion separation with high efficiency and flux. Issue 1 (February 2023) - Chen, Zehao; Zuo, Jihao; Zhao, Ting; Tan, Qing; Nong, Yunjun; Xu, Shouping; Cheng, Jiang; Wen, Xiufang; Pi, Pihui
Abstract: Developing separation materials with high separation efficiency and permeation flux for water-in-oil emulsions is an urgent demand and still a huge challenge. In this study, through anodization, electrostatic assembly of carbon nanotubes (CNTs), and grafting of nonafluorohexyltriethoxysilane (NFH-silane), a superhydrophobic copper foam containing re-entrant nanostructures was fabricated. The permeation channels were controllably extended by stacking multiple copper foams to form a columnar bed separator, and the residence time of emulsified water droplets was prolonged. When 30 pieces of copper foams were accumulated and the thickness of the stack was extended to 45 mm, the separation efficiency reached 99.14 %, and the permeation flux reached 31, 500 Lm −2 h −1 for separating surfactant-stabilized water-in-toluene emulsion. Due to the re-entrant nanostructures, the superhydrophobicity of the fabricated copper foam could keep stable in alkali, salt, oil environments, and only slightly decreased in surfactant environment, and the separation efficiency and flux can be recovered to the original level after multiple separation by simple cleaning, showing excellent superwettability stability and separation reusability. All these fascinating performance makes the superhydrophobic copper foam a promising candidate for continuous separating water-in-oil emulsions. Highlights: A superhydrophobic copper foam with re-entrant structure was prepared. The copper foams were stacked into a bed and exhibited high separation efficiency and permeation flux simultaneously. The mechanism of demulsification in the permeation channels was explained. The copper foam showed stable superwettability and separation performance can be restored after repeated treatment.